2013
DOI: 10.1590/s0104-66322013000400024
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the adsorption behavior of CO2-CH4 mixtures using activated carbon

Abstract: -Separation of CO 2 from CO 2 -CH 4 mixtures is an important issue in natural gas and biogas purification. The design of such separation processes depends on the knowledge of the behavior of multicomponent adsorption, particularly that of CO 2 -CH 4 mixtures. In this study, we present a series of experimental binary equilibrium isotherms for CO 2 -CH 4 mixtures on an activated carbon at 293 K and compare them with predicted values using the Ideal Adsorption Solution Theory (IAST) and the Extended Langmuir (EL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 39 publications
4
37
0
Order By: Relevance
“…Life cycle assessment [17] is an established technique for environmental analysis wherein system inputs (materials, energy, and others) are adequately correlated with the outputs (product, waste, and emissions) using standard methodologies with the aim of improving the system. However, LCA of waste treatments are often based on a single treatment technique coupled with uncertainties, which make them case specific with data unconnected to specific plant or functional scenarios [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Life cycle assessment [17] is an established technique for environmental analysis wherein system inputs (materials, energy, and others) are adequately correlated with the outputs (product, waste, and emissions) using standard methodologies with the aim of improving the system. However, LCA of waste treatments are often based on a single treatment technique coupled with uncertainties, which make them case specific with data unconnected to specific plant or functional scenarios [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…33 The IAS predictions strongly depend on the choice of the isotherm model applied for the description of single component adsorption isotherms. 7,12,[33][34][35][36][37][38] To avoid this Chen and Sholl 39 developed the transition matrix Monte Carlo (TMMC) approach but it can be applied only for simulated and not for experimental adsorption data.…”
Section: Introductionmentioning
confidence: 99%
“…Minimum and maximum CO 2 adsorption found to be 11% and 45% at 1 bar and 8 bar respectively. Low reduction of CO 2 may due to the fact that both CO 2 and CH 4 were absorbed by the material (Rios et al, 2013) and when the pressure increases, the material showed slight increase in adsorption of CO 2 than CH 4 . There is an initial and preferential filling of high-energy sites for which the more strongly adsorbed component (CO 2 ) is even more preferred in the competition for the sites than when competing for energetically weaker adsorption sites (Rios et al, 2013).…”
Section: Effect Of Biogas Inlet Pressure On Co 2 Reductionmentioning
confidence: 99%